Root and tuber crops in Belize - Serano, S. (International Center for Tropical Agriculture, 1986)
Since the cultivation of root and tuber crops in Belize is primarily at the subsistence level, there are no available data on research, production, and demand. Several data are presented on area sown, cropping systems, and socioeconomic profile of the farmers. Finally, the marketing of root crops and the factors affecting price fluctuation are analyzed and discussed. (CIAT)